2015
DOI: 10.1002/biof.1213
|View full text |Cite
|
Sign up to set email alerts
|

Taurine, a major amino acid of oyster, enhances linear bone growth in a mouse model of protein malnutrition

Abstract: Oysters (Oys) contain various beneficial components, such as, antioxidants and amino acids. However, the effects of Oys or taurine (Tau), a major amino acid in Oys on bone growth have not been determined. In the present study, we evaluated the effects of Oys or Tau on linear bone growth in a mouse model of protein malnutrition. To make the protein malnutrition in a mouse, we used a low protein diet. Growth plate thickness was increased by Oys or Tau. Bone volume/tissue volume, trabecular thickness, trabecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…Exact mechanism for the upregulation of IGF-1 by taurine is unclear in fishes. However, GH secretion of animals was induced by taurine in previous studies (Collu et al 1978;Ikuyama et al 1988;Huxtable 1992;Moon et al 2015). Also, production of IGF-1 in gilthead sea bream (Sparus aurata) was enhanced by GH administration (Pérez-Sánchez et al 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Exact mechanism for the upregulation of IGF-1 by taurine is unclear in fishes. However, GH secretion of animals was induced by taurine in previous studies (Collu et al 1978;Ikuyama et al 1988;Huxtable 1992;Moon et al 2015). Also, production of IGF-1 in gilthead sea bream (Sparus aurata) was enhanced by GH administration (Pérez-Sánchez et al 1994).…”
Section: Discussionmentioning
confidence: 95%
“…They suggested that the observed effect was conducted through the ERK2 signaling pathway. Moreover, Moon et al 23 observed that Tau over-expressed Insulin-like growth factor 1 (IGF-1) and serum level of IGF-1 through the phosphorylations of JAK2 and STAT5. They observed that these molecular changes enhance growth plate length, bone volume density (BV/TV), trabecular thickness (Tb.Th), and total porosity.…”
Section: Resultsmentioning
confidence: 99%
“…It is a sulfurated β-amino acid that is found in free form in animal sources 20 , 21 . It is documented that Tau is involved in calcium modulation, osmoregulation, antioxidation, membrane stabilization, neuromodulation, protein phosphorylation regulation 19 , 22 , 23 . Accordingly, in the current study, we aimed to combine the positive biological activities of electrospun (GNFs) and Tau with the structural features of the TIP-based scaffold to develop an innovative tissue engineering approach for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well known that oyster meat is a high-quality marine food resource that contains several vitamins and minerals [ 2 ]. Numerous studies have reported that oysters and their bioactive peptides have pharmacological benefits including anti-oxidant [ 3 ], anti-microbial [ 4 ], osteogenic [ 5 , 6 ], anti-inflammatory [ 7 ], postprandial blood glucose control [ 8 ], and anti-coagulant properties [ 1 ].…”
Section: Introductionmentioning
confidence: 99%